PENYELESAIAN SENGKETA KERUGIAN PIHAK KETIGA AKIBAT PERBUATAN HUKUM DEBITOR PAILIT - Ariyanto, Candra Fahmi (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2023)
Abstract Bankruptcy aims to provide legal certainty for creditors through the fair and balanced administration of bankruptcy assets. However, in bankruptcy practice, there are often legal actions by bankrupt debtors that cause losses to third parties, both before and during the process. The problem arises when Law Number 37 of 2004 concerning Bankruptcy and PKPU does not explicitly regulate the mechanism for resolving disputes over losses incurred by third parties as a result of the legal actions of bankrupt debtors, thus creating legal uncertainty. Using a normative legal research method with a legislative approach, conceptual approach, and case approach, specifically through an analysis of commercial court decisions related to the actions of bankrupt debtors that harm third parties. The settlement of disputes over losses to third parties resulting from the legal actions of bankrupt debtors can be pursued through two mechanisms. First, settlement based on the provisions of the UUK-PKPU if the act is directly related to the bankrupt estate. Second, through a lawsuit for unlawful acts based on Article 1365 of the Civil Code if it is not explicitly regulated in the UUK-PKPU, in order to provide legal protection for third parties. Keywords: Bankruptcy, Dispute, Unlawful Acts Abstrak Kepailitan bertujuan untuk memberikan kepastian hukum bagi kreditor melalui pengurusan harta pailit secara adil dan seimbang. Namun, dalam praktik kepailitan kerap terjadi perbuatan hukum debitor pailit yang menimbulkan kerugian bagi pihak ketiga, baik sebelum maupun selama proses berlangsung. Permasalahan muncul ketika Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan PKPU belum mengatur secara tegas mekanisme penyelesaian sengketa atas kerugian pihak ketiga akibat perbuatan hukum debitor pailit, sehingga menimbulkan ketidakpastian hukum. Menggunkan metode penelitian hukum normatif dengan Metode pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus, khususnya melalui analisis putusan pengadilan niaga terkait perbuatan debitor pailit yang merugikan pihak ketiga. Penyelesaian sengketa kerugian pihak ketiga akibat perbuatan hukum debitor pailit dapat ditempuh melalui dua mekanisme. Pertama, penyelesaian berdasarkan ketentuan UUK-PKPU apabila perbuatan tersebut berkaitan langsung dengan harta pailit. Kedua, melalui gugatan perbuatan melawan hukum berdasarkan Pasal 1365 BW apabila tidak diatur secara eksplisit dalam UUK-PKPU, guna memberikan perlindungan hukum bagi pihak ketiga. Kata Kunci: Kepailitan, Sengketa, Perbuatan Melawan Hukum